2008
DOI: 10.1007/s11172-008-0231-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structures of 5(3H)-oxotetrahydro-1H-imidazo[4,5-c][1,2,5]thiadiazole 2,2-dioxides

Abstract: The reactions of sulfamides with 4,5 dihydroxyimidazolidin 2 ones were studied at ambient and high pressure. The previously unknown derivatives of 5(3H) oxotetrahydro 1H imidazo [4,5 c] [1,2,5]thiadiazole 2,2 dioxide, viz., sulfo analogs of tetrahydroimidazo[4,5 d]imidazole 2,5 (1H,3H) diones (glycolurils), were synthesized. The structures of some of these compounds were established by X ray diffraction. The high pressure reactions performed under conditions of solvent phase transitions afforded also N (1,3 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…1-5 α Ureidoalkylation of thiosemicarbazide, aminoguanidine, and sulfamides yielded 5,7 dialkyl 3 thioxoperhydroimidazo [4,5 e] [1,2,4]tri azin 6 ones (1), 2 4,5 bis(thiosemicarbazido) and 4,5 bis (guanidinoamino)imidazolidin 2 ones (2, 3), 2 4 (guani dinoamino) and 4 (sulfonylimino)imidazolidin 2 ones (4-6), 2-4 and 5(3H) thioxotetrahydro 1H imidazo [4,5 c] [1,2,5]thiadiazole 2,2 dioxides (7). 5 Only few examples of the synthesis of glycoluril heteroanalogs by condensation of ureas with 4,5 dihydroxy imidazolidine 2 thiones (DHIT) have been published. 6,7 The present work is devoted to α thioureidoalkylation of urea heteroanalogs (thiosemicarbazide, aminoguani dine, sulfamide, and sulfonamides) with DHIT 8a-c and development of the synthetic methods towards novel imidazolidine 2 thione derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1-5 α Ureidoalkylation of thiosemicarbazide, aminoguanidine, and sulfamides yielded 5,7 dialkyl 3 thioxoperhydroimidazo [4,5 e] [1,2,4]tri azin 6 ones (1), 2 4,5 bis(thiosemicarbazido) and 4,5 bis (guanidinoamino)imidazolidin 2 ones (2, 3), 2 4 (guani dinoamino) and 4 (sulfonylimino)imidazolidin 2 ones (4-6), 2-4 and 5(3H) thioxotetrahydro 1H imidazo [4,5 c] [1,2,5]thiadiazole 2,2 dioxides (7). 5 Only few examples of the synthesis of glycoluril heteroanalogs by condensation of ureas with 4,5 dihydroxy imidazolidine 2 thiones (DHIT) have been published. 6,7 The present work is devoted to α thioureidoalkylation of urea heteroanalogs (thiosemicarbazide, aminoguani dine, sulfamide, and sulfonamides) with DHIT 8a-c and development of the synthetic methods towards novel imidazolidine 2 thione derivatives.…”
mentioning
confidence: 99%
“…It is known that the spontaneous sepa ration occurs provided the crystal of the corresponding compound contained homochiral molecule associates 14 formed preferably by strong hydrogen bonds. 5 Therefore, it was of interest to find whether this cation cation pattern remained on going from the C=O group to the C=S group that forms the hydrogen bonds that differ from those with the carbonyl group in the number and strength. 17, 18 Analysis of the geometry of dication 13b indicated that replacement of the oxygen atom by the sulfur atom resulted in the insignificant lengthening of the C(2)-N bonds (the difference did not exceed 0.03 Å) and in the change in the heterocycle conformation from the flat tened twist to the envelope (mean deviation of the C(5) atom is 0.24 Å).…”
mentioning
confidence: 99%
“…The synthesis of 1 (tetrahydro-1H-imidazo[4,5-c][1,2,5]thiadiazol-5(3H)-one 2,2-dioxide) was performed analogously according to a published report [30]: To a solution of sulfonamide (0.48 g, 5.0 mmol) in 8 mL dilute hydrochloric acid solution (pH = 6), L1 (0.59 g, 5.0 mmol) was added. The resulting mixture was heated to 60 °C and kept stirring for 12 h. After the reaction was completed, the reaction solution was cooled to 0 °C, and white solids (2) were precipitated, the yield is 0.62 g (69.6%).…”
Section: Synthesis Of Hexsmentioning
confidence: 99%
“…4,5 Dihydroxyimidazolidine 2 ones (DHI) are wide ly used as building blocks for the synthesis of various het erocyclic compounds, in particular, tetrahydroimidazo [4,5 d]imidazoles, 1-6 octahydroimidazo[4,5 e] 1,2,4 tri azines, 7,8 and tetrahydroimidazo[4,5 с] 1,2,5 thiadi azoles. 9, 10 The use of thio analogs of DHI, i.e., 4,5 dihydroxyim idazolidine 2 thiones (DHIT), in the synthesis of the cor responding heterocyclic systems is less studied because these compounds are less available. Among DHIT, those containing various aryl substituents at the N(1), N(3), C(4), and C(5) atoms have been studied the best.…”
mentioning
confidence: 99%
“…9, 10 The use of thio analogs of DHI, i.e., 4,5 dihydroxyim idazolidine 2 thiones (DHIT), in the synthesis of the cor responding heterocyclic systems is less studied because these compounds are less available. Among DHIT, those containing various aryl substituents at the N(1), N(3), C(4), and C(5) atoms have been studied the best.…”
mentioning
confidence: 99%